A new species of Pseudopaludicola (Anura, Leiuperidae) from western Piauí State, Northeast Brazil - Roberto, Igor Joventino (2013)
A new species of Pseudopaludicola from western Piauí State, Brazil, in the Cerrado domain is described. Pseudopaludicola parnaiba sp. nov. is a member of the genus Pseudopaludicola, on the basis of the presence of one hypertrophied antebrachial tubercle, posterolateral process of the hyoid outlined and epicoracoid cartilages slightly overlapped. The new species is characterized by an advertisement call composed of 6–46 non-pulsed notes per call and dominant frequency of 4794 ± 296 Hz, which supports an independent lineage. Additionally, the small size, body slender, toe tips knobbed with central groove, abdominal fold complete, tibio-tarsal articulation reaching the posterior border of the eye, and prepollex and prehallux composed of base and one element are character states that distinguish P. parnaiba from all the members of Pseudopaludicola. We provide its formal description with regard to external morphology, osteological characters and advertisement call.